Development of the Tailored Rett Intervention and Assessment Longitudinal (TRIAL) database and the Rett Evaluation of Symptoms and Treatments (REST) Questionnaire. Issue 6 (21st June 2017) - Santosh, Paramala; Lievesley, Kate; Fiori, Federico; Singh, Jatinder
Abstract : Introduction: Rett syndrome (RTT) is a pervasive neurodevelopmental disorder that presents with deficits in brain functioning leading to language and learning regression, characteristic hand stereotypies and developmental delay. Different mutations in the gene implicated in RTT— methyl-CpG-binding protein 2 ( MECP2 ) establishes RTT as a disorder with divergent symptomatology ranging from individuals with severe to milder phenotypes. A reliable and single multidimensional questionnaire is needed that can embrace all symptoms, and the relationships between them, and can map clinically meaningful data to symptomatology across the lifespan in patients with RTT. As part of the HealthTracker-based Tailored Rett Intervention and Assessment Longitudinal (TRIAL) database, the Rett Evaluation of Symptoms and Treatments (REST) Questionnaire will be able to marry with the physiological aspects of the disease obtained using wearable sensor technology, along with genetic and psychosocial data to stratify patients. Taken together, the web-based TRIAL database will empower clinicians and researchers with the confidence to delineate between different aspects of disorder symptomatology to streamline care pathways for individuals or for those patients entering clinical trials. This protocol describes the anticipated development of the REST questionnaire and the TRIAL database which links with the outcomes of the wearable sensor technology, and will serve as a barometer for longitudinal patient monitoring in patients with RTT. Methods and analysis: The US Food and Drug Administration Guidance for Patient-Reported Outcome Measures will be used as a template to inform the methodology of the study. It will follow an iterative framework that will include item/concept identification, item/concept elicitation in parent/carer-mediated focus groups, expert clinician feedback, web-based presentation of questionnaires, initial scale development, instrument refinement and instrument validation. Ethics and dissemination: The study has received favourable opinion from the National Health Service (NHS) Research Ethics Committee (REC): NHS Research Ethics Committee (REC)—London, Bromley Research Ethics Committee (reference: 15/LO/1772).